Gerenciamento de resíduos sólidos em laboratórios de química: caso de uma instituição de ensino superior - Gauza, Olga Regina (2019)
Chemistry is one of the sciences with great contribution to society, however; as a result of practical laboratory activities, that generate chemical residues with different levels of toxicity, it is seen to be necessary an effective management. Thus, the objective of this study was to critically evaluate the management of residues from teaching and research practices in didactic chemistry laboratories in a higher education institution. The research strategy involved data history analysis from 2008 to 2016, as well as information collection and monitoring in the years 2017 and 2018. The results of this study showed that from 2013 onwards there was an increase in waste generation due to the increase in the number of laboratories and teaching practices. Due to this, it was establishmed a Commission for Waste Management, the elaboration of a Solid Waste Management Program (SWMP), the preparation of a Waste Management Manual for users and managers, a new label establishment for labeling products and waste, and technical guidelines on responsible production. Lectures and guidelines were given to users and responsible personal for the laboratories which, in addition to having benefited from the training, also contributed to the proposition of new laboratory practices, with a view to rationalizing the waste generation generation. This research made it possible to identify opportunities for improvement in the management processes, among which was the change in laboratory practices routines that allowed the reduction in the consumption of chemical reagents, with a direct impact on associated costs. Reductions in the consumption of chemical reagents ranging from 50% to 100% were achieved, as well as the insertion of new waste reuse practices. Besides that, it was also proposed the creation of a waste inventory for the department, with a view to maximizing the reuse of these. It appears that the waste management system analyzed was effective, but it presents opportunities for improvement, especially regarding to reagent consumption and consequente generation of waste and associated costs.